Abbasid Gold Coins at the Bangladesh National Museum: A Numismatic and Historical Analysis - Md. Abdul Muhit; Abul Hasanat Md. Fazle Rabbi (International Journal of Social Science and Religion, 2025)
This article examines the numismatic and historical significance of eight unpublished Abbasid gold coins housed in the Bangladesh National Museum, focusing on their identification, inscriptional analysis, and historical relevance within the context of early Arab-Bengal trade relations. Discovered in 1996 and 2002 in the Chandpur and Brahmanbaria districts, adjacent to the historically significant archaeological site of Samatata, these coins have received little scholarly attention beyond basic acquisition records. The study employs a historical-numismatic approach, integrating primary sources such as the coins themselves and museum records with relevant secondary literature. It uncovers key numismatic details, including issuing authorities, minting origins, physical characteristics, and inscriptions affirming Islamic monotheism and venerating the Prophet Muhammad (SAW). Through analysis of these inscriptions, the study highlights notable features of Abbasid gold coinage and offers insights into the religious and political dynamics of the period. These coins serve as important material evidence within the broader historical context of early Arab interactions with ancient Bengal, particularly in the sphere of maritime commerce. References in Arab-Persian geographical texts further suggest Bengal's prominence as a commercial hub integrated into early Islamic trade networks. The discovery of these coins substantiates such accounts, illustrating the extent of Arab-Bengal trade relations from the eighth to the tenth centuries. Ultimately, the research situates these coins not merely as monetary instruments, but as artefacts of transregional connectivity and ideological dissemination during the early Islamic period.